Comparative analysis of subsampling methods for large mosquito samples - Jaworski, Linda; Jansen, Stephanie; Pfitzner, Wolf Peter; Beck, Matthias; Becker, Norbert; Schmidt-Chanasit, Jonas; Kiel, Ellen; Lühlen, Renke (Parasites & vectors, 2019)
The analysis of large mosquito samples is expensive and time-consuming, delaying the efficient timing of vector control measurements. Processing a fraction of a sample using a subsampling method can significantly reduce the processing effort. However, a comprehensive evaluation of the reliability of different subsampling methods is missing.
Gesehen am 17.01.2020
Keywords: Stechmücken